Bank loans non-linear structure of pricing: Empirical evidence from sovereign debts - Issam Hallak (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
The paper suggests an innovative contribution to the investigation of banking liabilities pricing contracted by sovereign agents. To address fundamental issues of banking, the study focuses on the determinants of the up-front fees (the up-front fee is a charge paid out at the signature of the loan arrangement). The investigation is based on a uniquely extensive sample of bank loans contracted or guaranteed by 58 less-developed countries sovereigns in the period from 1983 to 1997. The well detailed reports allow for the calculation of the equivalent yearly margin on the utilization period for all individual loan. The main findings suggest a significant impact of the renegotiation and agency costs on front-end borrowing payments. Unlike the sole interest spread, the all-in interest margin better takes account of these costs. The model estimates however suggest the non-linear pricing is hardly associated with an exogenous split-up intended by the borrower and his banker to cover up information. Instead the up-front payment is a liquidity transfer as described by Gorton and Kahn (2000) to compensate for renegotiation and monitoring costs. The second interesting result is that banks demand payment for all types of sovereign risk in an identical manner public debt holders do. The difference is that, unlike bond holders, bankers have the possibility to charge an up-front fee to compensate for renegotiation costs. Hence, beyond the information related issues, the higher complexity of the pricing design makes bank loan optimal for lenders on sovereign capital markets, especially relative to public debt, thus motivating for their presence. The paper contributes to the expanding literature on loan syndication and banking related issues. The study also has relevance for the investigation of the developing countries debt pricing.
urn:nbn:de:hebis:30-10388
Keywords: F34; G21; 330; Private debt; Sovereign debt; Syndicated loans; Up-front fees; Non-linear pricing design